2021
DOI: 10.1002/suco.202000494
|View full text |Cite
|
Sign up to set email alerts
|

Effect of steel fiber on the shear behavior of reinforced recycled aggregate concrete beams

Abstract: In this research, the influence of using steel fibers on the shear action of reinforced concrete beams, made of recycled concrete aggregate (RCA), was investigated through experiment and finite element analysis (FEA). First, 12 reinforced concrete beams were tested with varying amounts of steel fibers. These beams contained normal concrete aggregate (NCA) as reference beams besides RCA beams. All beam models had the same 150 mm x 250 mm cross‐section and 2000 mm length. The beams had three bars of 16 mm reinfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…It is an approach that has been widely used around the world in the last twenty years. On a global scale, concrete is a commonly used building material in civil engineering structures [7,15,[51][52][53][54][55]. Its use is increasing with the expansion of construction projects because of growing populations [44,[56][57][58][59].…”
Section: Recycled Aggregate Concrete (Rac)mentioning
confidence: 99%
“…It is an approach that has been widely used around the world in the last twenty years. On a global scale, concrete is a commonly used building material in civil engineering structures [7,15,[51][52][53][54][55]. Its use is increasing with the expansion of construction projects because of growing populations [44,[56][57][58][59].…”
Section: Recycled Aggregate Concrete (Rac)mentioning
confidence: 99%
“…1,2 It is also concrete which shows less resistance to flow, so it can be placed and compacted under its own weight without any vibration effort, even though it has sufficient viscosity to handle without segregation or bleeding. [3][4][5][6][7][8] SCC is extensively used around the world as it has opened up new fronts for the construction of various civil engineering structures. 9,10 SCC has been the most significant development in concrete technology in many ways recently.…”
Section: Introductionmentioning
confidence: 99%
“…Self‐compacting concrete (SCC) is a new type of concrete that reaches every corner in the formwork under self‐weight 1,2 . It is also concrete which shows less resistance to flow, so it can be placed and compacted under its own weight without any vibration effort, even though it has sufficient viscosity to handle without segregation or bleeding 3–8 . SCC is extensively used around the world as it has opened up new fronts for the construction of various civil engineering structures 9,10 .…”
Section: Introductionmentioning
confidence: 99%
“…It is now well‐known that incorporating steel fibers leads to an enhanced mechanical performance of concrete by improving crack propagation, ductility, and toughness of concrete 27–30 . Steel fiber can also reduce the general ecological effect of construction because of an improved maintenance life of structures manufactured with steel fiber‐reinforced concrete 31,32 .…”
Section: Introductionmentioning
confidence: 99%
“…Xie et al 39 presented that enhancement of flexural strength and toughness of recycled aggregate concrete incorporating steel fiber was better than those incorporating polypropylene fiber. Ibrahim et al 29 reported that using steel fiber by 0.5%, 1%, and 1.5% improved the shear strength of concrete containing 70% RCA by 24.5%, 40.6%, and 59.4%, respectively.…”
Section: Introductionmentioning
confidence: 99%